Training programs in university libraries: evolution and adaptation - Fernández-Ramos, Andrés (Anuario ThinkEPI, 2023)
Training programs developed by university libraries have gained prominence over time, overtaking other services and tasks traditionally performed by their employees. Greater user autonomy in relation to information (the search, evaluation, management, and use of) means a greater variety of sources, support, channels and information-producing agents, as well as new forms of teaching and learning, making it necessary to adapt traditional user training to the new needs of users and to the current technological context. In this sense, it is important to incorporate new content into training plans and take advantage of all teaching modalities at our disposal to provide this training in the most appropriate way and to reach the largest number of users.